Analysis of the Relationship Between Nurses' Knowledge of Infusion Therapy with the Incidence of Phlebitis and Patient Comfort - Sari, Intan Permata; Ginting , Chrismis Novalinda; Nasution , Sri Wahyuni (Newinera Publisher, 2024)
Phlebitis is a complication of infusion therapy. The aspect that affects the incidence of phlebitis and comfort is the nurse's skill of infusion therapy in inserting needles in the right location, right fluid, and right standard operating procedure. Nurses' skills in the infusion insertion were influenced mainly by knowledge. The research objective was to determine the relationship the nurse's knowledge of infusion therapy with the incidence of phlebitis and comfort. This type of research-correlational analytic with cross-sectional approach. The number of samples was 60 nurses who worked in inpatients ward and 60 patients who received infusion by a nurse. The results found that 51.7% of respondents had poor knowledge, the incidence of phlebitis was 46%.7, and as much as 48.3% of respondents felt comfortable with the insertion of an infusion done by the nurse. The results of further analysis showed that there is a significant relationship between knowledge of nurses about infusion therapy with incidence of phlebitis (p = 0.000), and there is a significant association between knowledge of the nurses and patients' comfort (p = 0.000). It was recommended for nurses to improve knowledge and skills so that the infusion complications and discomfort may be prevented.